The Development of Liveworksheets as Interactive Instructional Media for Teaching Reading Descriptive Texts at X Grade - Salsabilla Neva Larissa; Indah Tri Purwanti; Eliwarti Eliwarti; Zaldi Harfal (FKIP - Universitas Riau, 2026)
Technology's integration in education has transformed pedagogical approaches, particularly in the field of language acquisition. This research explores the use of Liveworksheets as an interactive educational resource for teaching Grade X students in descriptive texts. The aim is to create an effective and engaging learning tool to improve student understanding and motivation, while overcoming the limitations of conventional teaching approaches. This study uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation), excluding the Implementation phase. Experts in materials, media, and pedagogy evaluated the final product's quality to confirm its appropriateness. The validation results indicated that Liveworksheets is a highly valid educational tool, obtaining an average expert validation score of 3.5 and classified as “Highly Valid.” The results indicate that the integration of technology in educational settings enhances interactive learning and sustains student engagement. Moreover, the fully online format of Liveworksheets supports environmental sustainability by minimizing paper usage. This technology provides educators with an environmentally friendly alternative to traditional worksheets and fosters student-centered digital learning. Further study is required to investigate the implementation phase and measure its efficacy in educational contexts.